Direct Determination of Spatial Localization of Carriers in CdSe-CdS Quantum Dots. (27th August 2015) - Zhao, Yichen; Sugunan, Abhilash; Wang, Qin; Yang, Xuran; Rihtnesberg, David B.; Toprak, Muhammet S.
Abstract : Colloidal quantum dots (QDs) have gained significant attention due to their tunable band gap, simple solution processability, ease of scale-up, and low cost. By carefully choosing the materials, core-shell heterostructure QDs (HQDs) can be further synthesized with a controlled spatial spread of wave functions of the excited electrons and holes for various applications. Many investigations have been done to understand the exciton dynamics by optical characterizations. However, these spectroscopic data demonstrate that the spatial separation of the excitons cannot distinguish the distribution of excited electrons and holes. In this work, we report a simple and direct method to determine the localized holes and delocalized electrons in HQDs. The quasi-type-II CdSe-CdS core-shell QDs were synthesized via a thermolysis method. Poly(3-hexylthiophene) (P3HT) nanofiber and ZnO nanorods were selected as hole and electron conductor materials, respectively, and were combined with HQDs to form two different nanocomposites. Photoelectrical properties were evaluated under different environments via a quick and facile characterization method, confirming that the electrons in the HQDs were freely accessible at the surface of the nanocrystal, while the holes were confined within the CdSe core.